If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7z + -11 = 43 + z Reorder the terms: -11 + 7z = 43 + z Solving -11 + 7z = 43 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -11 + 7z + -1z = 43 + z + -1z Combine like terms: 7z + -1z = 6z -11 + 6z = 43 + z + -1z Combine like terms: z + -1z = 0 -11 + 6z = 43 + 0 -11 + 6z = 43 Add '11' to each side of the equation. -11 + 11 + 6z = 43 + 11 Combine like terms: -11 + 11 = 0 0 + 6z = 43 + 11 6z = 43 + 11 Combine like terms: 43 + 11 = 54 6z = 54 Divide each side by '6'. z = 9 Simplifying z = 9
| a^2+11a=12 | | ln(2x+-9)=0 | | 3s^2+28x-3=0 | | F(x)=x^2-15x+15 | | 43-26=40-x | | 5.2x=31 | | 17x+12=17x-12 | | 5.2x=32 | | (1)(2)y-7=(1)(5)y | | 56-21=x-20 | | 13+74=x+70 | | 7h+10=66 | | 43+15=40+c | | (3x+1)(6x-4)= | | .4w+60=w+53 | | X+16=20+17 | | -2(2t+1)=2 | | 48+x=47+31 | | .4w+60=1w+53 | | 9-8m=17 | | (x^2)-4x=6 | | 7m+1-1=4m+6m | | -3x+6x+24=9 | | 4+x=7+2 | | .4w+60=e+53 | | r+2r+3r=4 | | 4(f-8)=-16 | | 10m-21=79 | | V+15=7 | | 6z+3z=63 | | -3x+4=3 | | 8=8z |